Exploring psychopathy traits on intertemporal decision-making, neurophysiological correlates, and emotions on time estimation in community adults. Issue 7 (July 2022) - Moreira, Diana; Azeredo, Andreia; Barros, Susana; Barbosa, Fernando
Abstract: There are certain characteristics of psychopathy that may be related to changes in intertemporal choices. Specifically, traits such as impulsivity or lack of inhibitory control may be associated with a more pronounced discounting function in intertemporal choices (IC) and, in turn, this function may be based on changes in the basic mechanisms of time estimation (TE). Therefore, this study aimed to examine potential differences in neurophysiological correlates, specifically through N1, P3, and LPP measurements, which may be related to TE and IC, examining their modulation according to psychopathic traits, different emotional conditions, and different decision-making conditions. This experimental study included 67 adult participants (48 women) from the northern region of Portugal, who performed an intertemporal decision-making task and, of those, 19 participants (16 women), with a mean age of 25 years ( SD = 5.41) and a mean of 16 years of schooling ( SD = 3.37) performed the time estimation task. The instruments/measures applied were MoCA, used as a neurocognitive screening tool; the Triarchic Psychopathy Measure (TriPM), a self-report instrument with 58 items that map the core features of psychopathy along three facets – boldness, meanness, and disinhibition – and considers them continuously distributed among the general population; intertemporal decision-making and time estimation tasks – for the time estimation task, the stimuli consisted of 45 color images extracted from the Nencki Affective Picture System (NAPS). In the TE task, there was an almost significant effect of disinhibition on the values of θ, with higher values on this variable associated with greater values of θ in the unpleasant emotional condition. In the IC task, there were no significant effects of any psychopathy measure on the values of the gains and losses ratios. In addition, the analysis of the neurophysiological correlates of the IC task did not reveal a main effect of the decision-making condition, nor effects of any psychopathy measure on the N1 and P3 amplitudes. The analysis of the neurophysiological correlates of the TE task revealed that higher meanness values are associated with smaller N1 amplitude in the pleasant emotional condition, whereas higher disinhibition values are associated with greater N1 amplitude in the pleasant emotional condition. Still in this task, higher disinhibition values were associated with a smaller LPP amplitude in the unpleasant emotional condition. The increase in the distribution of attention resources towards time and/or the increase in activation states, including those originated by responses to emotional stimuli, may be the main factor that alters the way impulsive individuals and, presumably, individuals with high psychopathy, consider time when making decisions. Highlights: There are certain characteristics of psychopathy that may be related to changes in IC. Higher meanness values are associated with smaller N1 amplitude in the pleasant emotional condition (TE task). Higher disinhibition values are associated with greater N1 amplitude in the pleasant emotional condition (TE task). Higher disinhibition values were associated with a smaller LPP amplitude in the unpleasant emotional condition (TE task). Abstract : Psychopathy, Emotions, Time estimation, Decision-making, EEG